Penerapan Metode Demonstrasi Dan Tanya Jawab Dalam Meningkatkan Prestasi Belajar Kelas IV SD 4 Cranggang Dawe Kudus - Iswigati Martani (Lembaga Pendidikan Hikmatun Najah Blora, 2021)
The purpose of this study is to describe the application of the demonstration method and question and answer in improving the learning achievement of class IV SD 4 Cranggang Dawe Kudus. This research is Classroom Action Research (CAR). The subjects of this study were in 4th grade Cranggang State Elementary School with a total of 25 students. In this action research using the form proposed by Kemmis and Taggart. The implementation of this research was carried out in 2 cycles, each of which went through four stages, namely the planning stage, the implementation stage, the data collection stage and the reflection stage. Data collection techniques in this study are observation, interviews, tests and questionnaires. The results of pre-cycle research, cycle I, and cycle II researchers know that there has been an increase in the acquisition of learning outcomes. The results of pre-cycle learning are the number of students who complete with a score above 70 as many as 11 students or only 44% of classical class completeness. In the improvement of learning in the first stage of the first cycle, the number of students who completed with grades above 70 were 15 students or only 60% of the classical class completeness. And in the improvement of learning in the second phase of cycle II, the number of students who completed with a score above 70 were 19 students, and 84% had achieved classical completion.